ANALISIS SISTEM MANAJEMEN PERSEDIAAN OBAT-OBATAN A-VITAL DI INSTALASI FARMASI - , SANTI WIRASTRI HAYUHANING BUDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hospital is a medical institution providing health services such as inpatient, outpatient, and emergency department. Hospital should be able to improve the quality and affordable services to the community in order to manifest the degree of the highest health. Improving the quality of hospital services meant to improve the quality of service of each unit in the hospital, one of which is the pharmacy. The drug is an important item in the hospital because it can improve health status, raising confidence, and full engagement with helath services as well as a special commodity tha is expensive because almost 60% of the total hospital annual budget is used medicine. Moreover, private hospitals, such as PKU Muhammadiyah Pakem, that financial management be done independently. Inventory management system analysis is required to determine the exact order release of drugs, particularly class A-Vital, ie drugs that require most of the annual capital and should always be available at all times. The goal is to obtain optimal inventory. The study will compare Continuous Review System, Periodic Review System, and Hybrid System with SS and ROP determination using the best method among the Statistical Order Point and Maximum/Normal Demand Rate Approach. The results obtained show that there are 46 drugs that fall into the category A-Vital. Of the three methods were compared, Hybrid System is the most appropriate method for determining the order release inventory with the lowest total cost of Rp 498,539.00. Hybrid system also showed better results when compared with the existing system, evidenced by the total inventory costs lower by a margin of Rp 1,187,060.00 (70.45%), and 40 of drug A total of 46 drug-Vital has a value of TOR (Turn Over Ratio) higher.